1972
DOI: 10.1128/jb.111.1.287-289.1972
|View full text |Cite
|
Sign up to set email alerts
|

Use of Neomycin in the Isolation of Mutants Blocked in Energy Conservation in Escherichia coli

Abstract: A neomycin-resistant mutant of Escherichia coli K-12 unable to grow on Krebs cycle intermediates has been isolated. The mutant retained its respiratory capacity, but lacked membrane Mg 2+ -Ca 2+ -stimulated adenosine triphosphatase activity (EC 3.6.1.3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(50 citation statements)
references
References 12 publications
2
46
1
Order By: Relevance
“…The strains used in this report are all Lac +-transductants [11], of the parent A428 [1] and the mutants NI44 [1] and BV4 [2].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The strains used in this report are all Lac +-transductants [11], of the parent A428 [1] and the mutants NI44 [1] and BV4 [2].…”
Section: Methodsmentioning
confidence: 99%
“…A number of mutants ofEscherichia coli have been isolated with a defect in oxidative phosphorylation [1][2][3][4][5][6][7]. The mutants isolated thus far, all map in the same region of the chromosome (73.5 min) and all are affected in the membrane Mg 2÷-Ca 2+ ATPase complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that there is a relationship between resistance to neomycin and a defect in F 0 F 1 ATPase [18,19]. As the growth of the wildtype strain Lo84.13 was found to be dramatically reduced with 150 Wg ml 31 of neomycin sulfate, two sets of 10 10 colony forming units (CFU) were treated with a lethal concentration of 300 Wg ml 31 of neomycin.…”
Section: Isolation Of Mutants Defective In Membrane-bound Atpase Actimentioning
confidence: 99%
“…Fourthly, the manner in which such a variety of energy-uncoupled mutants may be isolated (e.g. [41,88,[99][100][101]) by selection for resistance to both charged and uncharged aminoglycoside antibiotics, suggests that the conformational state of at least part of the protoneural network modulates the rate at which such antibiotics are taken up by bacterial cells. Fifthly, it allows a ready harmonisation of the widely accepted general theory of protonic coupling with the perhaps controversial view [102] that the bulk-phase mitochondrial membrane potential during ATP synthesis is in fact energetically insignificant.…”
Section: Some Consequences Of the View Outlined Abovementioning
confidence: 99%